Evaluasi Kesesuaian Lahan untuk Pengembangan Tanaman Buah Naga di Kecamatan Tilatang Kamang - Asyifa, Ifni; Triyatno, Triyatno (Al-DYAS, 2024)
The purpose of this reseach are : 1) To analyze the suitability of the actual land of dragon fruit plants in Tilatang Kamang District, 2) To analyze the distribution pattern of dragon fruit plantation in Tilatang Kamang Diztrict. This type of research uses a quantitative descriptive approach with the fuzzy logic method to analyze land suitability and Nearest Neighbor analysis to analyze the distribution pattern of dragon fruit plantation. The results of the reseach are: 1) The suitability of dragon fruit crops obtained using fuzzy logic analysis obtained the area for the value of the land suitability index of the category not less than 0 – 0,59 has an area of 1.393,75 Ha with a percentage of 26,63% and for the category index is quite suitable to 0,6 – 0,79 has an area of 3.840,52 Ha with a percentage of 73,34%. 2) The distribution pattern of dragon fruit orchards in Tilatang Kamang District is a grouping pattern with the value of Nearest Neighbor Ratio = 0,31.